DEKOLONIALISASI GENDER: KAJIAN PERFORMATIS GENDER JUDITH BUTLER TERHADAP ISU LGBTIQ DAN IMPLIKASINYA BAGI PENDIDIKAN KRISTIANI - Revinola Enjelvestia Parebong; Orin Devisa (Institut Agama Kristen Negeri Toraja, 2024)
This article aims to describe gender decolonization based on Judith Butler's study of gender performativity regarding LGBTIQ issues and its implications for Christian Education. LGBTIQ emerged after the sexual revolution, previously referred to as the